Cultural Beliefs and Pregnancy Care among the Dayak Kenyah Community in East Kutai, Indonesia: An Ethnographic Study - Meihartati, Tuti; Ringgit, Ringgit; Sumiati, Sumiati; Abiyoga, Aries (Chakra Brahmanda Lentera Institute, 2026)
Background: Maternal health during pregnancy, childbirth, and the postpartum period serves as one of the key indicators of community well-being. Various studies have emphasized that cultural practices exert a significant influence on maternal care across different communities. This study aims to explore and analyze cultural beliefs and pregnancy care among the Dayak Kenyah community in East Kutai, Indonesia. Methods: This qualitative ethnographic study used purposive sampling with maximum variation. Data were gathered from 10 informants (6 pregnant women, 2 traditional leaders, 2 healthcare providers) through in-depth interviews and field notes. Analysis followed Braun and Clarke’s thematic approach. The study adheres to SRQR reporting guidelines to ensure rigor. Results: Five interpretive themes emerged: (1) Cultural Practices and Beliefs, involving dietary and behavioral taboos to protect against supernatural risks; (2) Traditional and Social Support, where traditional birth attendants (TBAs) provide physical and diagnostic assurance; (3) Integration with Formal Healthcare, highlighting midwives as cultural mediators; (4) Healthcare Quality Improvement, focusing on cultural competency to reduce stigma; and (5) Service Expectations, emphasizing a need for home-based care. Conclusion: Maternal care among the Dayak Kenyah is a hybrid process where ancestral rituals and clinical services coexist. Success in improving outcomes depends on integrating traditional practices with formal systems through culturally sensitive approaches.